The Effect of Feeding Red Beans In Yoghurt On Organoleptic Acceptance And Protein Levels - Yenni Okfrianti; Putri Ayu Lestari; Yunita Yunita (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Purpose: This study aims to examine the effect of red bean slurry addition on the organoleptic acceptance and protein content of yogurt. Methodology: The research employed a Completely Randomized Design (CRD) with one factor, namely variations in red bean slurry concentration. Organoleptic analysis was conducted using the Kruskal-Wallis test on attributes such as color, aroma, taste, consistency, and overall quality, involving 30 panelists. The most preferred product underwent protein content analysis using the micro Kjeldahl method. Results: Yogurt with 20% red bean slurry addition (F2) showed the highest organoleptic acceptance. The protein content of F2 yogurt increased from 0.56% to 1.30% after 24 hours of fermentation. Findings: The addition of 20% red bean slurry significantly enhanced the organoleptic acceptance and protein content of yogurt. Novelty: This study reveals the potential of red bean slurry as an additive to improve yogurt's organoleptic quality and protein content. Originality: This research contributes to the development of yogurt products enriched with red bean-based ingredients. Conclusions: Yogurt with 20% red bean slurry (F2) is the most preferred product, showing a significant increase in protein content after 24 hours of fermentation. Type of Paper: Experimental Research Paper.